THE MANAGER MULTIPLIER: EQUIPPING YOUR LEADERS TO DRIVE TEAM PERFORMANCE - Annisa Kurnianingsih; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
In today's competitive landscape, organizational performance is fundamentally linked to team efficacy, which is predominantly governed by frontline and middle managers. Despite their pivotal role, these "Manager Multipliers" are often under-equipped, having been promoted for technical proficiency rather than leadership capability, leading to a widespread "accidental manager" syndrome. This study aims to investigate the systematic equipping of managers as a primary lever for enhancing team performance, engagement, and talent retention. Employing a mixed-methodology approach—including a literature review, analysis of industry case studies, and synthesis of prevailing human capital metrics—the research identifies a five-pillar framework for manager development. The results indicate that strategic investment in manager selection, competency training, and support systems yields significant multiplicative returns on team outcomes, as measured by engagement scores, retention rates, and goal attainment. The discussion underscores that manager development must transition from an optional HR activity to a core business strategy. The conclusion asserts that cultivating Manager Multipliers is the highest-ROI investment for sustainable organizational growth, advocating for leadership accountability and a continuous learning culture.